A novel NBD-based pH "on–off" fluorescent probe equipped with the N-phenylpiperazine group for lysosome imaging. Issue 104 (31st October 2016) - Ma, Zhao; Lin, Yuxing; Chen, Hui; Du, Lupei; Li, Minyong
Abstract : A novel PET-based fluorescent probe (LN6 ) targeting to lysosome was found from the synthesized NBD derivatives. Abstract : A novel PET-based fluorescent probe (LN6 ) targeting to lysosome was found from the synthesized NBD derivatives. This probe was equipped with the novel lysosome-targeted N -phenylpiperazine group, and could be employed to image lysosome and detect its pH change without any washing steps.